Comparison of performance characteristics of C-MAC video, McCoy, and Macintosh laryngoscopes in elective cervical spine surgery - Shalini M Nair; Gokul Das Menon; Mathew George; Eldo Issac; Renjitha Bhaskaran (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: To compare the performance characteristics of C-MAC video, McCoy, and Macintosh laryngoscopes in elective cervical spine surgery. The primary objective was to assess the ease of intubation with the three study devices. The secondary objectives were the time to intubation and hemodynamic responses during intubation. Material and Methods : The prospective observational comparative study was conducted in a tertiary care hospital. Adult ASA 1 and 11 patients who underwent elective cervical spine surgery were included in the study. Patients with unstable spine and trauma were excluded. The analysis of variance, Bonferroni test, Chi square test and multiple comparison tests were used to compare the performance characteristics of laryngoscopes. Results: The C-MAC video laryngoscope improved glottis view by improving the modified Cormack-Lehane (CL) score and the percentage of glottis opening (POGO) score compared to McCoy and Macintosh laryngoscopes. The ease of intubation was better with the C-MAC video laryngoscope compared to the McCoy and Macintosh laryngoscopes. The time to intubation was comparable between the three laryngoscopes. The C-MAC video and McCoy laryngoscopes had 100% successful first attempt intubations while it was 90% for the Macintosh laryngoscope. Hemodynamic variables observed during intubation were comparable between the three groups. Conclusion: The use of C-MAC video laryngoscope resulted in better visualization of the glottis and easier tracheal intubation as compared to the Macintosh and McCoy laryngoscopes in cervical spine surgery. Both C-MAC video and McCoy laryngoscopes had 100% successful first attempt intubation.